(untitled) (Journal of Engineering, 2023)
The utilization of recycled brick tile powder as a replacement for conventional filler in the asphalt concrete mix has been studied in this research. This research evaluates the effectiveness of recycled brick tile powder and determines its optimum replacement level. Using recycled brick tile powder is significant from an environmental standpoint as it is a waste product from construction activities. Sixteen asphalt concrete samples were produced, and eight were soaked for a day. Samples contained 5% Bitumen, 2% to 5% brick tile powder, and conventional stone dust filler. The properties of samples were evaluated using the Marshall test. It was observed that the resistance to stiffness and deformation of asphalt concrete was increased by 99% when the conventional filler was replaced with brick tile powder. The resistance to deformation decreases as the percentage of brick tile powder increases while Marshall stability values increase significantly. At an optimum content of 4% recycled brick tile powder as filler, the Marshall stability is increased by 123%. Based on this investigation, it is established that brick tile powder can be effectively used in asphaltic concrete as a filler. This presents a sustainable solution to waste utilization and pavement performance.